Comparison of the adherence of nontypeable haemophilus influenzae to lung epithelial cells - Yuwei Rong; Zihao Liu; Heping Wang; Zuguo Zhao (BMC Infectious Diseases, 2024)
Abstract Objective Nontypeable Haemophilus influenzae (NTHi) plays an important role in respiratory tract infections, and adherence to lung epithelial cells is the first step in lung infections. To explore the role of NTHi in childhood lung infections, a comparative study was conducted on the adherence of strains isolated from sputum culture and bronchoalveolar lavage fluid to A549 lung epithelial cells. Methods Haemophilus influenzae strains were obtained from the sample bank of Shenzhen Children’s Hospital, and identified as NTHi via PCR detection of the capsule gene bexA. NTHi obtained from healthy children’s nasopharyngeal swabs culture were selected as the control group, and a comparative study was conducted on the adherence of strains isolated from sputum culture or bronchoalveolar lavage fluid of patients to A549 cells. Results The adherence bacterial counts of NTHi isolated from the nasopharyngeal cultures of healthy children to A549 cells was 58.2 CFU. In patients with lung diseases, NTHi isolated from bronchoalveolar lavage fluid was 104.3 CFU, and from sputum cultures was 115.1 CFU, both of which were significantly higher in their adherence to A549 cells compared to the strains isolated from the healthy control group. There was no significant difference in adherence between the strains isolated from sputum cultures and bronchoalveolar lavage fluid (t = 0.5217, p = 0.6033). Conclusion NTHi played an important role in childhood pulmonary infections by enhancing its adherence to lung epithelial cells.